Pengaruh Menyikat Gigi Terhadap Indek’s DMF-T, Status Kebersihan Gigi Dan Mulut (OHI-S) dan Jenis Makanan Kariogeni - Rusmali, Rusmali; Sartika, Mery; Herlina, Rita (LPPM Institut Pendidikan Nusantara Global, 2024)
According to the West Kalimantan Provincial Health Service, the individual DMF-T index for residents of West Kalimantan in 2017 recorded 6-7 cases of dental and oral health, the results of research by Rusmali, et al. in 2022 regarding the individual DMF-T index were greater than 3(30.9%). Dental and oral hygiene status (OHI-s) criteria were poor (27.6%) and moderate at 45.3%, while the type of cariogenic food frequently consumed was 45.9%. This type of quantitative is to analyze the effect of tooth brushing on the DMF-T index, OHI-s status and types of cariogenic foods that are often consumed every day, the tools used are survey sheets and questionnaires, the method used is Purposive sampling, univariate, bivariate analysis and multivariate with Regression test. The results are that on average residents brush their teeth twice a day (67.7%), their individual DMF-T index is 3-5 (32.3%), OHI-s status is medium criteria (48%), consume cariogenic foods (38 .9%), Adjt R2 value (0.9%), correlation number R (0.8) is close to 1.